Comparative clinical study of laparoscopic assisted vaginal hysterectomy and non-descent vaginal hysterectomy - Shiragur, Shobha S.; Rajammal, B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Laparoscopic assisted vaginal hysterectomy (LAVH) is increasingly becoming popular. It's really a technique made to replace abdominal hysterectomy. The need of the hour is the minimal invasive surgery, early discharge from the hospital, early resumption of work, avoidance of disfiguring scar on the abdomen and cost-effectiveness of the procedure which are as important as cure of the disease. The objective of this study is to compare the effectiveness and safety of laparoscopic and vaginal hysterectomies for non-descent uteri (NDVH). Methods: The study was undertaken in the department of obstetrics and gynecology, Amrita Institute of Medical Sciences, Kochi for the period of one year. About 50 women in each group undergoing LAVH and NDVH for benign pelvic conditions were studied preoperatively, intra-operatively and post-operatively in detail for indications, operative time, intraoperative blood loss, duration of stay in hospital. Results: The mean operative time in LAVH was 240.6 minutes and in NDVH 168.3 minutes. Minimum duration of stay was in LAVH 3 days and in NDVH 4 days. Mean duration of stay in both groups was 6.4 days. Maximum duration of stay-15 days in both groups. Conclusions: LAVH is a better approach for a larger uterus whereas NDVH is preferable for a small uterus, not only for shorter operative time and minimal wound, but also for much lower costs.